Inside Paul Auster’s Crypt: Autobiography and Spectrality in Ghosts - Giorgos GIANNAKOPOULOS (E-REA)
Ghosts, the second novel in Paul Auster’s The New York Trilogy, can be read as a fictionalized theoretical speculation on autobiography, one that problematizes such oppositions as the auto- and hetero- of biography, the self and the other, the writing of one’s life and the writing of one’s death. Auster’s writing practices resonate with Jacques Derrida’s insights into the nature of autobiography. Reflecting and complicating his own autobiographical writing, Auster’s early novel assumes the form of a postmodern detective story playing on the motif of criticism that views the criminal as author and the detective as reader while rendering both roles unstable and interchangeable. Detective and criminal are both effects of linguistic operations, trapped in the textual web that is woven around and between them, as texts, letters, and reports circulate and are dispatched in order to return to the sender according to the logic of what Derrida has termed the postal principle.